2018
DOI: 10.1108/ijoem-10-2016-0259
|View full text |Cite
|
Sign up to set email alerts
|

Impact of public intervention on micro and small enterprises performance in Ethiopia

Abstract: Purpose The effectiveness of any government interventions to support small firms is always a concern in achieving improvements in enterprise performances. The purpose of this paper is to evaluate thoroughly the impact of micro and small enterprises’ (MSEs’) support programs on core intermediate and final outcomes of interest. Design/methodology/approach The impact evaluation employs a non-parametric matching procedure for parametric outcome analysis using the propensity score matching (PSM) method. Aiming at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…The Program Intensity variable shows positive and significant values throughout 2020 to 2022, indicating that an increase of 1 program attended can increase business profits by 20.4% in 2020, 20.5% in 2021, and 8.67% in 2022. These findings are the same with the research by Yonis et al (2018), which found that participating in government programs can encourage MSMEs to foster innovative business approaches and enhance resource development procedures. This can also be seen in Table 3, where participants who attended all programs had the highest average profits.…”
Section: Gita Krisnawati and Sartika Djamaluddinsupporting
confidence: 87%
“…The Program Intensity variable shows positive and significant values throughout 2020 to 2022, indicating that an increase of 1 program attended can increase business profits by 20.4% in 2020, 20.5% in 2021, and 8.67% in 2022. These findings are the same with the research by Yonis et al (2018), which found that participating in government programs can encourage MSMEs to foster innovative business approaches and enhance resource development procedures. This can also be seen in Table 3, where participants who attended all programs had the highest average profits.…”
Section: Gita Krisnawati and Sartika Djamaluddinsupporting
confidence: 87%
“…This result assured that the youngest owners' enterprises were more successful than the other group. This finding is consistent with the finding of Yonis et al (2018), but contradicts with the result of Aworemi et al (2010). Therefore, the age of the owners was able to predict the growth of MSEs.…”
Section: Discussionsupporting
confidence: 68%
“…The old people may be engaged in different responsibilities, and they may reject the activities of their business. As cited by Yonis et al (2018), there is a negative relationship between the performances of MSEs with the age of the owners. The young owners become successful than the old ones (Nejati et al, 2014).…”
Section: Agementioning
confidence: 95%
See 1 more Smart Citation
“…Despite the growing body of literature investigating the investment support policy contribution to competitiveness and efficiency of subsidised firms, e.g., references [21][22][23][24][25][26][27][28][29][30], the minority of studies focuses specifically on productivity effects, e.g., references [31][32][33][34][35]. The productivity assessment using only the labour productivity indicator, as common in a number of studies, e.g., references [25,[36][37][38][39][40], may bias the overall productivity effects. Bernini et al [32] argue that labour productivity may increase because of the capital deepening induced by the subsidy, whereas the efficiency of all inputs used may not increase at all.…”
Section: Introductionmentioning
confidence: 99%